Targeting Lactate Dehydrogenase-B as a Strategy to Fight Cancer: Identification of Potential Inhibitors by In Silico Analysis and In Vitro Screening - Manos Vlasiou; Vicky Nicolaidou; Christos Papaneophytou (MDPI AG, 2023)
Lactate dehydrogenase (LDH) is an enzyme that catalyzes the reversible conversion of lactate to pyruvate while reducing NAD+ to NADH (or oxidizing NADH to NAD+). Due to its central role in the Warburg effect, LDH-A isoform has been considered a promising target for treating several types of cancer. However, research on inhibitors targeting LDH-B isoform is still limited, despite the enzyme's implication in the development of specific cancer types such as breast and lung cancer. This study aimed to identify small-molecule compounds that specifically inhibit LDH-B. Our in silico analysis identified eight commercially available compounds that may affect LDH-B activity. The best five candidates, namely tucatinib, capmatinib, moxidectin, rifampicin, and acetyldigoxin, were evaluated further in vitro. Our results revealed that two compounds, viz., tucatinib and capmatinib, currently used for treating breast and lung cancer, respectively, could also act as inhibitors of LDH-B. Both compounds inhibited LDH-B activity through an uncompetitive mechanism, as observed in in vitro experiments. Molecular dynamics studies further support these findings. Together, our results suggest that two known drugs currently being used to treat specific cancer types may have a dual effect and target more than one enzyme that facilitates the development of these types of cancers. Furthermore, the results of this study could be used as a new starting point for identifying more potent and specific LDH-B inhibitors.